2015
DOI: 10.1038/nmeth.3430
|View full text |Cite
|
Sign up to set email alerts
|

Traction microscopy to identify force modulation in subresolution adhesions

Abstract: We present a reconstruction algorithm that resolves cellular tractions in diffraction-limited nascent adhesions (NAs). The enabling method is the introduction of sparsity regularization to the solution of the inverse problem, which suppresses noise without underestimating traction magnitude. We show that NAs transmit a distinguishable amount of traction and that NA maturation depends on traction growth rate. A software package implementing this numerical approach is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
208
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(226 citation statements)
references
References 34 publications
8
208
1
1
Order By: Relevance
“…4B). Such a value corresponds to the range of stress that cells are able to generate on their substrate 41,42 and therefore supports the relevance of the present system in mimicking the mechanical coupling of neighbouring cells through their matrix 43 . In terms of force, magneto-active substrates can locally transmit nN-forces to cell adhesions, if a typical adhesion surface of 1µm 2 is considered, which also compares to forces generated by single adhesions 44,45 .…”
Section: Generation Of the Magnetic Fieldsupporting
confidence: 78%
“…4B). Such a value corresponds to the range of stress that cells are able to generate on their substrate 41,42 and therefore supports the relevance of the present system in mimicking the mechanical coupling of neighbouring cells through their matrix 43 . In terms of force, magneto-active substrates can locally transmit nN-forces to cell adhesions, if a typical adhesion surface of 1µm 2 is considered, which also compares to forces generated by single adhesions 44,45 .…”
Section: Generation Of the Magnetic Fieldsupporting
confidence: 78%
“…For this reason, intense efforts have been devoted to understanding how key signaling molecules and ECM characteristics influence the formation and growth of FAs. In particular, in vitro studies using elastic hydrogels have shown that forces generated by actomyosin contraction are essential for the stabilization of FAs (5,6). Numerous observations have convincingly demonstrated that cells form larger FAs as well as develop higher intracellular traction forces on stiffer ECMs (7,8), evidencing the mechanosensitive nature of FAs which has been quantitatively modeled using different (continuum, coarse-grain, and molecular) approaches (9,10).…”
mentioning
confidence: 99%
“…Common substrates used for TFM include polyacrylamide or silicon based gels. They are selected due to their linear elasticity, optical transparency, and tunability of elastic moduli through polymer chain crosslinking, over several orders of magnitude [95]. Knowing the elastic moduli of the substrates, the displacement field can be converted to a traction force field using an inverse method [93, 96,97].…”
Section: Techniques To Study Cell–cell Adhesionmentioning
confidence: 99%